Foreword - Sipalla, Humphrey S (Strathmore Law Journal, 2017)
Punches of the invisible fist: Intra- and inter-personal relations in the neo-liberalised African university. There can be no independent thought–indeed no independence–without institutions to sustain independent research and produce relevant knowledge. The key institution is the research university